Tectonics of frame systems in the costume of the 15th–19th century - Berezova Marina A.; Belko Tatiana V. (Архитектон, 2025)
The article examines the frame systems that formed the silhouette of a women's costume from the 15th to the 19th century. The study focuses on the design features of skirts, which served as a spatial framework and gave the costume a characteristic volume. The work offers a typology of constructive solutions based on historical examples and reveals the principles of tectonic logic underlying the design of the volume of skirts. The types of frame systems of closed and open structures are identified and described: hoop, quilted, folded, tensegrity, mesh, hinged and spiral. The results of the analysis can be applied in the field of modern costume, especially in the field of experimental design that works with shape, volume and silhouette transformation.